Estudo da expressão de citocinas, quimiocinas e metaloproteinases e associação da ocorrência de seus polimorfismos, em reabsorções radiculares inflamatórias e por substituição após reimplante de dentes permanentes - Juliana Vilela Bastos (2014)
External root resorption (ERR) is a serious complication following replantation and its progressive forms - inflammatory external root resorption (IERR) and replacement external root resorption (RERR) - quite often lead to tooth loss with relevant functional, aesthetic, psychosocial and economic consequences. Not much is known about the role of the host immune response in the prognosis of tooth replantation. Considering the pivotal role of soluble factors in controlling mineralized tissue resorption the aim of the present study was to identify and quantify cytokines, chemokines and MMPs in teeth showing different patterns of ERR. In addition, patients genotype in SNPs in genes that code for these factors, along with demographic and clinical factors, were evaluated for their possible influence in the occurrence, extension and progression of RRE in 205 replanted permanent mature teeth from 165 patients treated at the Dental Trauma Clinic at the School of Dentistry of Federal University of Minas Gerais (DTC SD FUMG) in Belo Horizonte, Brazil. Our working hypothesis was that these immunological and genetic factors influenced differently the occurrence of IERR and RERR. Patients older than 16 years at the moment of trauma had a lower chance of developing IERR (OR 0.23 IC 95% 0.08 0.65 p= 0.005) and also had lower rates of RERR progression in the long term (HR 0.29 IC 95% 0.13 0.67 p=0.004). Patients under 11 years of age had a higher chance of developing severe IERR before the onset of endodontic therapy (OR 0.36 IC 95% 0.15 0.85 p=0.02). Each day that elapsed between the replantation and the pulp extirpation increased the risk of severe IERR by 0.5% per day but did not affected RERR progression. Wet storage media, especially milk (HR 0.30 IC 95% 0.15 0.64 p= 0.002) had a protective effect, while prolonged periods of extra-alveolar storage (HR 2.97 IC 95% 1.0 -8.83 p= 0.049) and splinting time (HR 1.002 IC 95% 1.00-1.003 p=0.04) determined faster progression of RRE in the long term. SNPs in the IL10 (OR 0.35 IC 95% 0.13-0.94 p = 0.038) and TNFSR11B (OR 0.28 IC 95% 0.09 0.93 p=0.038) genes were associated with the occurrence and extension of IERR observed at the onset of endodontic therapy. SNPs in the IL1A (RTF 1.87 IC 95% 0.99-3.51 p=0.054) was also associated with the faster progression of RRE in the long term. Teeth bearing RRE irrespective of the type, showed higher levels of IL-1RA, IL-6, IL-8, IFN, TNF, TGF, CCL5, RANK e OPG when compared to the control group (no resorption). Teeth bearing IERR showed higher levels of IL-1 (p=0,02) and TNF- (p<0,001) when compared to teeth with RERR. MMP2 was found in higher concentrations in the RERR group when compared with EIRR (p<0,001). In conclusion our results confirmed that age at the moment of trauma and timing of pulpectomy are important risk factors for IERR prior to the onset of endodontic therapy. Storage condition of the avulsed teeth, splinting time and age at the moment of trauma had a marked effect on the rate of RERR progression in the long term. Taken together our results suggested that local factors that modulate bone resorption acted differently in IERR and RERR and that the patients genetic profile may contribute in the outcome after tooth replantation.